2004
DOI: 10.1143/jjap.43.1149
|View full text |Cite
|
Sign up to set email alerts
|

Energy Control of Incident Ions to the Chamber-Wall by Using Push–Pull Bias (Phase-Controlled Bias) in UHF-ECR Etching System

Abstract: The effect of Push–Pull bias (phase-controlled bias) on the plasma potential and sputtering at the chamber-wall was investigated. It was found that the plasma potential could be controlled unrelated to the geometrical configuration of the chamber by using phase-controlled bias. The reason is that by using phase-controlled bias in the plasma with a magnetic field, the earth function of both electrodes facing each other can be controlled. Specifically, with the phase difference set to 180 degrees, the plasma pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the previous study, it was reported that chamber wall sputtering and plasma diffusion can be suppressed by maintaining RF phase differences of 180 . [5][6][7] Typical upper and lower RF bias powers at 800 kHz in this experiment were 600 and 1500 W, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study, it was reported that chamber wall sputtering and plasma diffusion can be suppressed by maintaining RF phase differences of 180 . [5][6][7] Typical upper and lower RF bias powers at 800 kHz in this experiment were 600 and 1500 W, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A 200-MHz power supply and a 4-MHz antenna-bias power are introduced to the upper antenna, and a 4-MHz RF-bias power is supplied to the bottom electrode. The phase of each bias is controlled to confine the plasma electrically [2]. The interaction between the plasma and reactor wall is suppressed by this phasecontrolled bias system, so long-term stability of the etching performance is expected.…”
Section: Issues In 400-hr Runmentioning
confidence: 99%
“…18 In that work, the phase-controlled 800 kHz bias was applied both to the antenna and wafer electrodes, while ion-energy distributions on the grounded wall were measured with an ion-energy analyzer. 18 In that work, the phase-controlled 800 kHz bias was applied both to the antenna and wafer electrodes, while ion-energy distributions on the grounded wall were measured with an ion-energy analyzer.…”
Section: Introductionmentioning
confidence: 99%